9.5k views
2 votes
What is the answer for 10-6(5-2y)

User DrGenius
by
5.8k points

2 Answers

3 votes

Answer:


12y-20

Explanation:

First, we need to distribute.


= 10+(-6)(5)+(-6)(-2y)= 10+-30+12y

Now, we need to combine these terms.


=10+-30+12y=(12y)+(10+-30)=12y+-20

The answer is


12y-20

User Salil Pandit
by
5.0k points
1 vote

Answer:

-20 + 12y

Explanation:

Equation: 10 - 6(5 - 2y)

Step 1:

10 - 30 + 12y Multiply (5 - 2y) by -6 (distributive property)

Step 2:

-20 + 12y Subtract 10 by 30 (10 - 30 = -20)

User Andrei Astrouski
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.